Role of opioid signaling in kidney damage during the development of salt-induced hypertension - Golosova, Daria (Life Sci Alliance, 2020)
Opioid use is associated with predictors of poor cardiorenal outcomes. However, little is known about the direct impact of opioids on podocytes and renal function, especially in the context of hypertension and CKD. We hypothesize that stimulation of opioid receptors (ORs) contributes to dysregulation of intracellular calcium ([Ca(2+)](i)) homeostasis in podocytes, thus aggravating the development of renal damage in hypertensive conditions. Herein, freshly isolated glomeruli from Dahl salt-sensitive (SS) rats and human kidneys, as well as immortalized human podocytes, were used to elucidate the contribution of specific ORs to calcium influx. Stimulation of κ-ORs, but not μ-ORs or δ-ORs, evoked a [Ca(2+)](i) transient in podocytes, potentially through the activation of TRPC6 channels. κ-OR agonist BRL52537 was used to assess the long-term effect in SS rats fed a high-salt diet. Hypertensive rats chronically treated with BRL52537 exhibited [Ca(2+)](i) overload in podocytes, nephrinuria, albuminuria, changes in electrolyte balance, and augmented blood pressure. These data demonstrate that the κ-OR/TRPC6 signaling directly influences podocyte calcium handling, provoking the development of kidney injury in the opioid-treated hypertensive cohort.